Comparison of practical methods for an efficient FPGA implementation of STAP. Issue 8 (3rd August 2019) - Hasanikhah, Narjes; Amin-Nejad, Siavash; Darvish, Ghafar; Moniri, M.R.
ABSTRACT: In this paper, practical methods for an efficient field programmable gate array (FPGA) implementation of space-time adaptive processing (STAP) are investigated and compared. The most important part for calculating the STAP weights is QR decomposition (QRD) which can be implemented using the modified Gram–Schmidt algorithm. Investigations show the method that uses QRD with less computational burden and leads to more effective implementation. Its structure parameterised with vector size to create a trade-off between hardware and performance factors. For this purpose, the modifications on QRD-MGS are performed in order to speed increasing. Then, the calculation of STAP weight vector was implemented. The implementation results show that decreasing vector size decreases the resources utilisation, computational burden and consumption power. However, computation time increases slightly, but the update rate of the STAP weights is maintained. For example, weights in the system with 6 antenna arrays, 10 received pulses and 200 range samples computed in 262 µs by vector size of 17 on the Arria10 FPGA the maximum of which is 155 µs are related to QRD-MGS and 107 µs is related to other parts. Therefore, QRD-MGS is the most important part in calculation of the STAP weight vector and its simplifying led to an efficient implementation. Abbreviations : Computation time, Field programmable gate array, QR decomposition, Space time adaptive processing